Losing My Religion: A Call for Help by Jeffrey Lang (Beltsville, MD: amana publications, 2004. 504 pages.) (American Journal of Islam and Society, 2005)
Jeffrey Lang is a well-known Muslim convert and professor of mathematicsat the University of Kansas. Losing My Religion is his third book. In many ways, it surpasses the first two in the relevance and urgency of its subject matter.While the book shares its title with a 1991 song by the popular rockband REM, its central theme is almost as old as religion itself: bridging thechasm that seems to separate religious beliefs and practices on the one hand,and contemporary rationality and secular culture on the other. Perhapsbecause of his background in mathematics, Lang is confident that humanreason, if properly used, can and will affirm the truths of divine revelation.The idea is by no means new, though its application has always called forthe most rigorous efforts by the most sophisticated human intellects.Writing as a lay theologian, Lang makes some interesting points inLosing My Religion, which is primarily aimed at the general North AmericanMuslim community. The main impetus behind this book is the alienationexperienced by young Muslims and converts who are confronted with thetraditional and conservative forms of Islam presented (and vigorouslydefended) by the immigrant-dominated mosque culture. This alienationaccounts for the facts that the majority of second- and third-generationMuslims tend to stay away from mosques and that it is generally the olderimmigrants or very recent arrivals who seem to be active in these institutions.Lang rightly argues that the young people’s absence from the mainstreamof the Muslim community’s religious and social life represents a seriousthreat to Islam’s survival and growth in North America ...